Anteseden yang Mempengaruhi Mobile Game Loyalty dan Dampaknya terhadap In-App Purchase Intention - Nur Arif Munadie; Teguh Widodo (BISMA (Bisnis dan Manajemen), 2019)
Mobile technology has become something inseparable thing from everyday life. One feature of mobile technology that often used is gaming applications or also called mobile games, this technology using behavior creates opportunities for every business involved in the mobile game industry. The growth of mobile games usage in addition to creating opportunities also creates challenges in the form of competition from other business actors in the same industry. In order to win the competition, a strategy that can be used to meet consumer expectations of value of the product which ultimately leads to the urge to make a purchase is needed. This study aims to measure the influence of values perceived by consumers and loyalty as a mediator of purchase intentions in consumers of mobile games in Indonesia. Structural Equation Modeling (SEM) was used for this study. Tests were carried on 207 players in Indonesia with the characteristics of never having previously purchased in-app purchases. The results showed that the playfulness variable had a positive and significant impact on loyalty. The connectedness variable had a positive and significant impact on good price, loyalty, and in-app purchase intention, and the good price variable had a positive and significant impact on in-app purchase intention.